DIVERSITAS GOLONGAN DARAH SISTEM ABO BERDASARKAN RIWAYAT DEMAM BERDARAH DENGUE PADA MAHASISWA DI PADANG HARAPAN KOTA BENGKULU - Irawan, Putra Adi; Krisyanella, Krisyanella (Politeknik Kesehatan Kemenkes Bengkulu, 2020)
Abstract Background: Diversity of blood groups based on certain diseases such as dengue is still a concern by a number of researchers. Dengue hemorrhagic fever is still a national health problem. Indonesia is one of the countries that has relatively high dengue cases. Bengkulu Province was previously ranked 26th with a 17.53 morbidity rate in 2017, rising to 3rd place with a morbidity rate of 72.28 per 100,000 population in 2018. Data for the last two (2) years shows that Bengkulu City is one of the areas with the most cases of DHF. Data on the diversity of blood groups in the ABO system based on a history of dengue fever in Padang Harapan, Bengkulu City is still very lacking. There is no definite data either in the relevant Office or Regional and Provincial Hospitals, while cases of Dengue Fever occurs at a rate that fluctuates every year Methods: This study was a non-experimental study with an analytic observational design using a cross-sectional approach. Respondents were students in Padang Harapan, Bengkulu City who were selected based on the inclusion and exclusion criteria of 391 people using purposive sampling technique with an age range of 17-25 years. The study took place from March to November 2020. Blood group data and history of dengue fever were collected using google form and confirmed by laboratory examination. Results: The diversity of blood groups in ABO system students was dominated by blood groups A (32.5%), O (31.2%), B (25.6%), and AB (10.7%). As much as 9.7% of students in Padang Harapan (n = 391) have experienced dengue fever. The diversity of blood groups of students who had dengue fever (n = 38) was dominated by blood type A (44.7%), B (28.9%), O (18.4%), and AB (7.9%). Conclusion: There is a significant relationship (P=0.032) between blood groups and a history of DHF.